(3TQM OjhGf GdeJfHis - (3CHi GdMSf Ydj Hf CMeO Hf eMeO Hf Ydj GdhGMOis; (3GdeJfHj , CHh GdWjH,J (B354 (3g` s ((3YeQh Hf jhSa Hf Ndjd Hf GdMGL HTQ s)
(3ChdgG (B:s
(3CeG HYO aEfi deG QCjJ aMhd GdYdeGA ebHdjf Ydi TYQ CHj GdWjH CMeO Hf GdMSjfi GdeJfHi Ohf ZjQg s
(3BNQgG (B:s
(3Gddg GYde HGdUhGH gPG BNQ eG GTJed Ydjg OjhGf TYQ GdPi QJHg HfaSg hgh NeSI BdGa hCQHY eFI hCQHYI hJSYhf bGajg s
(3GdfSNI HgG MhGTs
(3HChdgG HNW eZGjQ eMOK Cfg(B" (3GdGeY GdYRjRj(B" (3TQM CHj GdYdGA GdeYQjs
(3hGdUMjM eG CKHJg GdeagQSs
(3HChdgG agQS ddbUGFO hHBNQ GdUaMGJ JYbjHg s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3GdCOHs